2021
DOI: 10.3389/fncel.2021.660523
|View full text |Cite
|
Sign up to set email alerts
|

Microglia in Health and Disease: The Strength to Be Diverse and Reactive

Abstract: Microglia are the resident immune effector cells of the central nervous system (CNS) rapidly reacting to any perturbation in order to maintain CNS homeostasis. Although their outstanding reactive properties have been elucidated over the last decades, their heterogeneity in healthy tissue, such as across brain regions, as well as their diversity in the development and progression of brain diseases, are currently opening new avenues to understand the cellular and functional states of microglia subsets in a conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 69 publications
(104 reference statements)
0
21
0
1
Order By: Relevance
“…In neurological disease and models thereof, the term “disease‐associated microglia” (DAM) defines molecular microglial states, as reflected by a gene expression signature, that are associated with these diseases and may modulate their pathologies (Hakim et al, 2021 ; Hammond et al, 2019 ; Keren‐Shaul et al, 2017 ; Mathys et al, 2017 ; Mrdjen et al, 2018 ; Tay et al, 2018 ; Uriarte Huarte et al, 2021 ). Some DAM genes show expression changes common to many diseases, while others may only change in a specific disease, or at specific time points across one or many diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In neurological disease and models thereof, the term “disease‐associated microglia” (DAM) defines molecular microglial states, as reflected by a gene expression signature, that are associated with these diseases and may modulate their pathologies (Hakim et al, 2021 ; Hammond et al, 2019 ; Keren‐Shaul et al, 2017 ; Mathys et al, 2017 ; Mrdjen et al, 2018 ; Tay et al, 2018 ; Uriarte Huarte et al, 2021 ). Some DAM genes show expression changes common to many diseases, while others may only change in a specific disease, or at specific time points across one or many diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Initially assumed to be excessively activated in response to amyloid deposition and neuronal dysfunction, evidence indicates that microglia actively participate in AD pathogenesis since disease early stages ( Fan et al, 2017 ). The identification of new potential therapeutic microglial targets ( Sierksma et al, 2020 ), as well as the classification of several microglial subtypes in health and disease ( Uriarte Huarte et al, 2021 ), created new opportunities for immunomodulation-based strategies in opposition to previous approaches based on counteracting or inducing a unique phenotype ( Deczkowska et al, 2018 ). However, the lack of translation from the bench to the clinic is still one of the most limiting factors for the success of drug development in AD ( Vitek et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) identified AD onset risk loci that are associated with genes involved in microglia physiology and responses, such as CR1 (complement receptor type 1), SPI1 (transcription factor PU.1), TREM2 (triggering receptor expressed on myeloid cells 2) and CD33 [ 61 ]. New technologies such as single cell RNA-sequencing, have redefined the roles and phenotypes of microglia in brain disorders and unveiled a complex regional and temporal heterogeneity of their signatures across mouse models and neurodegenerative conditions in human [ 7 , 56 , 69 , 76 , 90 ]. PET imaging correlated microglia activation with hippocampal volume loss [ 25 ] but if and how microglia play a role in the subregional deterioration pattern of AD is poorly understood.…”
Section: Introductionmentioning
confidence: 99%